THE ROLE OF EMOTION AND IMAGINATION IN ROMANTICISM - Eldorbek Erkin og’li Khamitov; Markabaeva Mexriban Keulimjayevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines the significant role of emotion and imagination in Romantic literature. Romanticism, which developed in the late 18th and early 19th centuries, focused on individual feelings, personal experiences, and the creative power of the imagination. Unlike previous literary movements that emphasized logic and reason, Romantic  writers  valued  emotions  as  a  source  of  inspiration,  truth,  and  artistic expression. Their works often explore the connection between human feelings, nature, and creativity. Emotion is a central element in Romantic literature. Writers depict strong and deep  feelings  such  as  love,  sorrow,  happiness,  and  despair,  allowing  readers  to understand the inner world of the characters. Emotions are not only used to describe personal  experiences  but  also  to  reflect  on  social  issues,  moral  questions,  and  the human  condition.  Romantic  writers  believed  that  literature  gains  authenticity  and power when it expresses true emotions. Imagination  is  another  core  aspect  of  Romanticism.  Through  imagination, writers  explore  abstract  ideas,  create  symbolic  and  fantastical  worlds,  and  express thoughts beyond everyday life. Imagination is used to depict nature, dreams, fantasy, and  even  supernatural  elements,  providing  readers  with  a  rich  and  meaningful understanding of human experiences. It allows writers to go beyond reality, reflect creatively, and convey deep emotional truths. The relationship between emotion and imagination is especially important in Romantic literature. Emotions inspire creativity, while imagination gives structure and meaning to feelings. Together, they create expressive and memorable narratives that explore human psychology, ethical questions, and the beauty of the world. Romantic writers  also  stress  individuality,  personal  freedom,  and  authenticity,  showing characters who follow their hearts and seek personal truth. In  conclusion,  emotion  and  imagination  are  essential  components  of Romanticism. Romantic literature highlights the importance of personal experience, creativity, and feelings, providing readers with a deeper understanding of human nature and  the  mind.  By  combining  emotion  with  imagination,  Romantic  writers  produce literature that is moving, reflective, and inspiring, encouraging readers to connect with their own emotions, think creatively, and appreciate the beauty and complexity of life.